INDUCCIÓN DE LA OVULACIÓN EN LLAMASMEDIANTE LA ADMINISTRACIÓN INTRAMUSCULAR DEL PLASMA SEMINAL DE LLAMA, ALPACAY TORO - López F., Alicia (2012)
Female llama without calf at foot, in good reproductive conditions and bearing a follicle ³7 mm in the ovaries, detected by ultrasonography, were selected (n = 64). All animals were administered 5 mg of LH(Lutropin V) to synchronize the newly emergent follicular wave.Asecond ultrasonography evaluation was done 12 days later to confirm the presence of a dominant follicle (³7mm) and then, animalswere randomlydistributed into four groups. The first three groups were i.m. injected (2 ml)with llama, alpaca and bull seminal plasma, respectively, and the fourth group was injected with PBS (phosphate basic serum) and remained as control. The occurrence of ovulation was evaluated two days later.All animals injectedwith llama and alpaca seminal plasma ovulated, whereas only 25% of llamas treated with bull seminal plasma, and none of the control group ovulated. The size of the corpus luteum 9 days after treatment did not vary among the treated groups. The results indicated that the i.m. administration of llama and alpaca seminal plasma, and in lesser degree, the bull seminal plasma induce ovulation in the llama and allow the growth of a corpus luteum to a size proper of these species.